Effectiveness of Problem Based Learning to Improve The Results of Learning Indonesian Language - Siti Choiriyah (Universitas Sebelas Maret, 2020)
The focus of this Class Action Research is the application of Problem Based Learning on The Results of Learning Bahasa Indonesia Grade 5 SDN Karanganyar 01 Tugu Subdistrict Semarang Year 2019/2020. From the above formulation of research objectives for (1) Describing the application of the use of PPT media in improving student learning achievement (2) Describing how to improve students' learning motivation, especially the content of Indonesian language lessons. The implementation of learning improvements carried out in three cycles of each cycle shows an improvement in learning outcomes. From the data obtained, it can be concluded that the use of Problem Based Learning on the results of learning Bahasa Indonesia grade 5 SDN Karanganyar 01 Tugu Subdistrict Semarang is very effectively used to improve student learning outcomes.